Retro-Molar Trigonal Reconstruction and Oncologic Outcomes after Resection of Large Malignant Ulcers in Elderly Patients - Sameh Roshdy; Mohamed T Hafez; Islam A El Zahaby; Osama Hussein; Fayez Shahatto; Mosab Shetiwy; Shadi Awny; Sherif Kotb; Hend A El-Hadaad; Adel Denewer (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2015)
Background: Buccal mucosa carcinoma represents 3 to 5% of oral-cavity cancer. Retromolar buccal trigon affected in one third of patients with buccal mucosal cancers. Squamous cell carcinoma is the commonest pathological finding.  Aim: The research was designed to study suitability of submental island flap and radial forearm free flap (RFFF) as one stage reconstructive procedure after resection of large retromolar-trigonal cancers. And to assess locoregional recurrence and disease free survival after adjuvant treatment.  Methods and techniques: Fifty three patients with retromolar-trigonal cancer underwent resection with safety margins, cervical block neck dissection and reconstruction with submental island flap and radial forearm free flap (RFFF) in oncology center Mansoura University from August 2010 to May 2014.  Results: Seven patients underwent RFFF, 46 patients reconstructed with sub-mental flap. Partial necrosis was encountered in 5 cases of sub-mental flaps but lost flaps were present in 2 cases of RFFF. 14 patients received neoadjuvant chemotherapy, 33 patients received postoperative radiotherapy. Local recurrence was 13.2%, 2 year disease free survival (DFS) was 72.7%.